986. Incidence of Invasive Fungal Infections in Previously Untreated Patients with Acute Myeloid Leukemia Receiving Venetoclax and Azacitadine. (4th December 2021) - Phupitakphol, Tanit; Johnson, Tanner M; Abbott, Diana; Gutman, Jonathan; Pollyea, Daniel; Koullias, Yiannis
Abstract: Background: Acute myeloid leukemia (AML) is associated with poor prognosis, particularly in elderly patients with co-morbidities. Low-intensity therapies like azacitidine (aza) were the standard of care and were associated with low response rates and limited survival. Combining venetoclax (ven) with aza demonstrated significant improvements in responses and survival compared to aza alone, and represents the new standard of care for this population. However, as a myelosuppressive regimen, infectious complications, especially invasive fungal infections (IFI), are a potential concern. The incidence of IFI and the role for antifungal prophylaxis have not been well defined for newly-diagnosed AML patients receiving ven/aza. Methods: We conducted a retrospective cohort review of AML patients treated with ven/aza at the University of Colorado Hospital from January 2014 to August 2020. Duration of therapy was defined as the time from initiation of treatment through one of the following endpoints (1) patient discontinuation, (2) progression of disease, (3) bone marrow transplantation, or (4) death. Four patients with a history of prior IFI were excluded. We assessed the impact of patient age, sex, duration of neutropenia, antifungal prophylaxis, and AML specific risk factors on the incidence of IFI as defined by the European Mycoses Study Group. Results: One hundred forty-four AML patients were included in the study. Ten patients received antifungal prophylaxis and none developed IFI (p=0.21). Twenty-five (17%) patients developed IFI: 2 (8%) had proven IFI, 6 (24%) probable IFI, and 17 (68%) possible IFI. Invasive pulmonary aspergillosis represented all 25 cases of proven, probable, and possible IFI. There was a statistically significant association between prolonged neutropenia ( >60 days) and IFI (p=0.007), whereas age, sex, and SWOG classification were not significantly associated with IFI. Conclusion: The incidence of IFI in our AML cohorts treated with ven/aza was 17%, lower than that reported at other institutions. Neutropenia > 60 days was significantly associated with IFI in our AML cohort treated with ven/aza. Although we were not powered to determine whether antifungal prophylaxis impacted IFI, there was no significant difference in IFI for patients who received prophylaxis. Disclosures: All Authors : No reported disclosures